Comparison of Glucose ORS with and without Rice Based ORS in Treatment of Acute Gastroenteritis from 6 Month to 5 Years - Sabika Iftikhar, Maqsood Ahmad, Aafia Khalid, Nagham Nawaz Awan, Muhammad Shahid Jamil (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Acute gastroenteritis-related diarrhea is a major contributor to pediatric morbidity and mortality. Although the success of various oral rehydration formulations varies and the treatment of choice ultimately depends on the underlying reason, oral rehydration remains crucial for efficient early therapies. Objective: To compare outcome of Glucose ORS with and without rice based ORS in treatment of acute gastroenteritis from 6 month to 5 years in terms of mean stool frequency. Study Design: Randomized clinical trial Settings: The study will be done at department of Peads Ittifaq Hospital Lahore from 9 December 2018 to 19 June 2019. Sample Technique: Non probability consecutive sampling Methodology: Children of both sexes were included in this analysis of gastroenteritis cases between the ages of 6 months and 5 years. They divided into two separate groups. For 48 hours, group A was given G-ORS, whereas group B was given rice soup. Over the course of 48 hours, the typical individual needs to use the washroom. Results: Eighty people took part in the study (forty in each group). There were 25 males in Group A (40.02%), and 26 in Group B (50.98%). The average ages of those in Group A and Group B were very comparable (3.30±1.18 vs. 2.07±1.03 years, p=0.29). The baseline stool frequency of Group A was 4.11±2.33, while that of Group B was 5.01±2.81 (p= 0.51). Group A also had a higher mean weight, at 6.87±1.97, than Group B, at 6.28±2.01. Group A had an average of 2.15±0.77 bowel movements in 48 hours, while Group B had an average of 2.08±0.73 (p=0.91). The mean frequency was 2.170.78 for males, 2.14±0.69 for females, and 2.11±0.72 for both sexes combined (p=0.91). There were no statistically significant differences in age, BMI over 10, or baseline frequency. Practical implication: The purpose of this research was to more exactly explain the authentic benefit of rice-based ORS in comparison to glucose ORS and to evaluate whether or not there is significant differences. Conclusion: Both groups reduced the number of incidences of the confounding variable roughly at the same rate, and there was no statistically significant difference between them either in terms of that reduction or in terms of stratification of any of the study’s other confounding variables. Keywords: G-ORS, Gastroenteritis, Stool frequency, Rice soup